Ethiopia : Country Procurement Assessment Report, Volume 2. Data and Analysis - World Bank (Washington, DC, 2013)
The CPAR has reviewed the Ethiopian procurement system against the generally accepted international principles of sound procurement fiduciary management, meeting the criteria of transparency, economy and efficiency necessary for an optimal use of scarce public funds. These criteria are: (i) existence of a comprehensive and transparent legal framework, including a clear, well defined organizational structure to ensure the application of procurement laws with adequate monitoring; (ii) the use of modernized procurement procedures and practices; (iii) a proficient and evenly distributed procurement staff; (iv) existence of an independent control mechanism, including a functioning system to treat bidders' complaints and carry out independent audits, and (v) anti-corruption measures with effective sanctions. Using these benchmarks, the team has found that these criteria are only partially satisfied in Ethiopia, and that improvements are necessary.